2017
DOI: 10.30612/agrarian.v10i37.6782
|View full text |Cite
|
Sign up to set email alerts
|

A heterogeneidade tecnológica da pecuária leiteira em Minas Gerais

Abstract: A heterogeneidade dos sistemas de produção de leite de Minas Gerais é uma das causas de instabilidade das relações comerciais da cadeia produtiva e das dificuldades de direcionamento de políticas públicas. Neste sentido, objetivo deste trabalho foi caracterizar espacialmente a heterogeneidade tecnológica dos sistemas de produção de leite das 66 microrregiões do estado de Minas Gerais. Para isso, estimou-se um modelo fatorial a partir de 15 variáveis de tecnologia e de escala de produção e foi construído um Índ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Milk production occurs on 1.2 million farms (23% of all farms) that are widely dispersed throughout the country, reflecting a diverse set of social, cultural, and climatic factors (IBGE, 2017). As a result, dairy farms are heterogeneous in terms of technology adoption intensity and production scale (Silva et al, 2016;Simões et al, 2017;Telles et al, 2017). According to Gomes (2006) 'technological duality' is a prominent feature in Brazilian milk production because farmers using higher-productivity technology operate side by side with farmers using low-input, low-output systems with limited adoption of newer available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Milk production occurs on 1.2 million farms (23% of all farms) that are widely dispersed throughout the country, reflecting a diverse set of social, cultural, and climatic factors (IBGE, 2017). As a result, dairy farms are heterogeneous in terms of technology adoption intensity and production scale (Silva et al, 2016;Simões et al, 2017;Telles et al, 2017). According to Gomes (2006) 'technological duality' is a prominent feature in Brazilian milk production because farmers using higher-productivity technology operate side by side with farmers using low-input, low-output systems with limited adoption of newer available technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Esta padronização consistiu em adquirir médias iguais a zero (0,0) e desvios padrões iguais a um (1,0). Desta forma é possível evitar problemas decorrentes de desigualdade das unidades de medidas das variáveis e estabilizar as variâncias para a determinação das cargas fatoriais (FIELD, 2009;SIMÕES et al, 2017). A tabela 10 demonstra a correlação altamente significativa (P<0,01) entre as variáveis estudadas, onde foi estimado um score fatorial para cada tratamento através da multiplicação do valor das variáveis padronizadas pelo coeficiente do score fatorial correspondente (FÁVERO et al, 2009;HAIR et al, 2009).…”
Section: Resultsunclassified
“…The four factors made similar contributions to explaining the total variance of the dataset and, consequently, the variability between dairy farms of the studied region. Previous studies have shown that similar technological aspects are important in distinguishing dairy farms in Brazil (Gabbi et al, 2013;Neumann et al, 2016;Simões et al, 2017;Zimpel et al, 2017) and other developing countries (García et al, 2012;Janssen & Swinnen, 2017;Rangel et al, 2020).…”
Section: Discussionmentioning
confidence: 98%